Integrated Marketing Communication And Mapping of Tourism Destinations In Larike Village - Roy A Wattimena; Julius Buyang; Agus K Soetrisno; Evandro Adolf W Manuputty; Dian Utami Sutiksno (International Journal of Management Research and Economics, 2024)
One service industry that makes a substantial financial contribution to the nation's economy is tourism. The province of Maluku has tourism potential. including a tourist attraction in the town of Larike, which is located in Ambon City, Maluku Province's Central Maluku area. The purpose of this study is to map and assess the use of integrated marketing communication in Larike Village tourism attractions. This kind of study uses qualitative approaches and applied research.